Analisis kebijakan ekonomi digital indonesia dalam mendukung pembangunan berkelanjutan: Perspektif inklusi digital dan transformasi UMKM - Ridha Ramadhany; Abdul Halim; Sri Mujiarti Ulfah; Murraya Putri Palupi; Aditia Pebrian (Journal of Economics Research and Policy Studies, 2026)
This study aims to analyze digital economic policies in Indonesia from a sustainable development perspective using a systematic literature review. The results show that digital economic policies contribute to economic growth by strengthening digital infrastructure, digitizing MSMEs, and increasing financial inclusion. However, the impact is still dominated by economic aspects rather than social and environmental dimensions. This study identifies the digital divide between regions and introduces the concept of the digital inclusion paradox, a condition where policies designed to expand access actually have the potential to create new exclusions due to limited access, digital literacy, and technological adaptation capacity. Furthermore, a gap was found between policy objectives and their implementation, particularly regarding the equitable distribution of benefits, governance, and integration of environmental aspects. These findings emphasize that digital transformation does not always result in equitable inclusion, thus requiring more integrated, inclusive, and sustainable policies to support equitable development in Indonesia.